Genetic risk Factors of systemic lupus erythematosus in the Malaysian population: a minireview - Hwa Chia, C.; Maude Elvira, P.; Chua, K.H. (2012)
SLE is an autoimmune disease that is not uncommon in Malaysia. In contrast to Malays and Indians, the Chinese seem to be most affected. SLE is characterized by deficiency of body's immune response that leads to production of autoantibodies and failure of immune complex clearance. This minireview attempts to summarize the association of several candidate genes with risk for SLE in the Malaysian population and discuss the genetic heterogeneity that exists locally in Asians and in comparison with SLE in Caucasians. Several groups of researchers have been actively investigating genes that are associated with SLE susceptibility in the Malaysian population by screening possible reported candidate genes across the SLE patients and healthy controls. These candidate genes include MHC genes and genes encoding complement components, TNF, FcÎ³R, T-cell receptors, and interleukins. However, most of the polymorphisms investigated in these genes did not show significant associations with susceptibility to SLE in the Malaysian scenario, except for those occurring in MHC genes and genes coding for TNF-Î±, IL-1Î², IL-1RN, and IL-6.